Realizing real-time optical molecular imaging in peripheral nerve tissue via Rhodamine B - Wei, Jinzheng; Guo, Xinyu; Wang, Yixi; Zhang, Yunmeng; Zhao, Wei; Han, Shufeng; Liu, Chao; Yang, Xiaofeng; Liang, Wenkai (Frontiers in Medicine, 2024)
Background: Iatrogenic nerve injury is a consequential complication during surgery. Thus, real-time imaging of peripheral nerve (PN) possesses significant clinical implications. In recent years, the rapid advancements in optical molecular imaging (OMI) technology have provided essential technical foundations for the implementation of PN fluorescence imaging. This study aimed to realize real-time OMI of PNs via Rhodamine B.Results: The excitation peak of Rhodamine B in PBS, NS, 5%GS, and FBS formulations was 554 nm, and the emission peak was 576 nm. In PBS group, the maximum SBR was 15.37±0.68 while the dose of Rhodamine B was 8 nmol. Through ex-vivo validation on fresh human nerve tissue and verification using mouse and human tissue sections, we observed fluorescent signals of Rhodamine Bin the regions of nerve tissue and the fluorescence signals were all concentrated on the neuronal cell membranes. After injection, the fluorescent signal in nerve tissue reached its peak at 24 hours (h), coinciding with the highest SBR (5.93±0.92) in mouse nerve tissues at this time point. Additionally, the fluorescence signal could be maintained for at least 48 h. Within 24 h, lung dilation and fusion of alveoli occurred. Then these pathological manifestations gradually diminished, returning to normal at 2 weeks (w), with no significant acute or chronic adverse reactions observed in other tissues.